Algorithms and Discrete Applied Mathematics First International Conference, CALDAM 2015, Kanpur, India, February 8-10, 2015. Proceedings - Ganguly, Sumit; Krishnamurti, Ramesh (Theoretical Computer Science and General Issues,, 2015)
This book collects the refereed proceedings of the First International Conference onon Algorithms and Discrete Applied Mathematics, CALDAM 2015, held in Kanpur, India, in February 2015. The volume contains 26 full revised papers from 58 submissions along with 2 invited talks presented at the conference.The workshop covered a diverse range of topics on algorithms and discrete mathematics, including computational geometry, algorithms including approximation algorithms, graph theory and computational complexity.